2021
DOI: 10.1111/tri.13934
|View full text |Cite
|
Sign up to set email alerts
|

Kidney transplant recipient perspectives on telehealth during the COVID‐19 pandemic

Abstract: Summary The COVID‐19 pandemic has challenged the delivery of health services. Telehealth allows delivery of care without in‐person contacts and minimizes the risk of vial transmission. We aimed to describe the perspectives of kidney transplant recipients on the benefits, challenges, and risks of telehealth. We conducted five online focus groups with 34 kidney transplant recipients who had experienced a telehealth appointment. Transcripts were thematically analyzed. We identified five themes: minimizing burden … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(53 citation statements)
references
References 31 publications
(32 reference statements)
1
52
0
Order By: Relevance
“…A total of eight studies published between August 2010 and August 2021 were included in this scoping review. Two studies used a cross‐sectional design (Alshaer et al, 2020; Campbell et al, 2012), two used a mixed‐methods design (Lunney et al, 2021; Qiu et al, 2021), and four used a qualitative design (Huuskes et al, 2021, Lunney et al, 2020; Trace et al, 2020; Varsi et al, 2021). The studies were conducted in the United Kingdom, Canada, Australia, and Norway.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of eight studies published between August 2010 and August 2021 were included in this scoping review. Two studies used a cross‐sectional design (Alshaer et al, 2020; Campbell et al, 2012), two used a mixed‐methods design (Lunney et al, 2021; Qiu et al, 2021), and four used a qualitative design (Huuskes et al, 2021, Lunney et al, 2020; Trace et al, 2020; Varsi et al, 2021). The studies were conducted in the United Kingdom, Canada, Australia, and Norway.…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of remote consultations for patients were identified in seven studies included in this review. The most widely reported benefit was the convenience of remote consultations (Alshaer et al, 2020; Huuskes et al, 2021; Lunney et al, 2020; Qiu et al, 2021; Varsi et al, 2021). Participants reported that video consultations reduced the burden of appointment waiting time and time spent travelling.…”
Section: Resultsmentioning
confidence: 99%
“… 222 Despite this, half of kidney transplant recipients worried more about their health and a third wanted to postpone hospital appointments to minimize their risk of COVID-19, 222 , 223 noting the benefits of telehealth. 224 …”
Section: Psychological Impact Of the Pandemic On Patients And Staffmentioning
confidence: 99%
“…222 Despite this, half of kidney transplant recipients worried more about their health and a third wanted to postpone hospital appointments to minimize their risk of COVID-19, 222,223 noting the benefits of telehealth. 224 For patients on the waiting list, the suspension of transplant programs left some feeling disappointed and helpless with concerns their health could deteriorate. 225 Although most patients were in favor of waiting list reactivation, this was not universal, highlighting the need for individualized discussions as the pandemic picture evolves.…”
Section: Psychological Impact Of the Pandemic On Patients And Staffmentioning
confidence: 99%
“…Australian patients also report that the telephone has mainly been used for telehealth appointments [ 17 , 18 ] with this also true for cancer appointments [ 10 , 19 ]. Despite the greater use of the telephone, Australian surveys have shown that patients generally accept telehealth, appreciating it as a strategy for reducing risks during the COVID-19 pandemic [ 10 , 17 , 20 , 21 ]. However, the lack of a physical examination [ 1 , 22 ] and concerns regarding its impersonal nature are noted as barriers and reasons why many patients say they will return to in-person appointments [ 10 , 20 ].…”
Section: Introductionmentioning
confidence: 99%